2018
DOI: 10.1021/acs.energyfuels.8b02659
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature and Single-Step Synthesis of N-Doped Porous Carbons with a High CO2 Adsorption Performance by Sodium Amide Activation

Abstract: In this study, N-enriched porous carbons were prepared by a facile synthesis method at low temperatures ranging from 400 to 500 °C. Sodium amide was used as both activator and nitridation reagent, and lotus stalk was used as the carbon precursor. The as-synthesized samples demonstrate the maximum CO2 uptake of 3.88 and 5.62 mmol/g at 25 and 0 °C, respectively, at atmospheric pressure. Moreover, these lotus stalk-derived adsorbents exhibit a rapid CO2 adsorption rate, high CO2/N2 selectivity, moderate CO2 isost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…The presence of N can not only provide Lewis basic active sites, but also increase the carbon framework polarity, which is beneficial for CO 2 /CH 4 /N 2 selectivity adsorption [21,23,35,37]. It should be stressed that N-5 was the main type of N species in the carbons, which is beneficial to boosting the CO 2 capture [21,35,60]. Moreover, the high-resolution spectra of C1s ( Figure S1a boosting the CO2 capture [21,35,60].…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The presence of N can not only provide Lewis basic active sites, but also increase the carbon framework polarity, which is beneficial for CO 2 /CH 4 /N 2 selectivity adsorption [21,23,35,37]. It should be stressed that N-5 was the main type of N species in the carbons, which is beneficial to boosting the CO 2 capture [21,35,60]. Moreover, the high-resolution spectra of C1s ( Figure S1a boosting the CO2 capture [21,35,60].…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure 5c, d and e, three sub-peaks are visible in the deconvoluted XPS N1s spectra: Pyridinic-N (N-6) at 398.5 eV, pyrrolic-/pyridonic-N (N-5) at 399.9 eV, and pyridine-N-oxide (N-X) at 402 eV, respectively [21,30,58,39]. The presence of N can not only provide Lewis basic active sites, but also increase the carbon framework polarity, which is beneficial for CO2/CH4/N2 selectivity adsorption [21,23,35,37]. It should be stressed that N-5 was the main type of N species in the carbons, which is beneficial to a Specific surface area calculated by Brunauer−Emmett−Teller (BET) method; b total pore volume obtained at P/P 0 0.99; c cumulative pore volume calculated in the range of pore widths up to 2 nm; d cumulative pore volume calculated in the range of pore widths up to 1 nm; e obtained from C, H, and N elemental analysis; f calculated by difference.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some previous studies, sodium amide (NaNH 2 ) was found to be both an activator and a nitrogen source. [22][23][24] Compared with potassium hydroxide (KOH), using NaNH 2 as an activator, is less corrosive to the equipment. At the same time, the activation temperature was lower (T < 600 C).…”
Section: Introductionmentioning
confidence: 99%